Basic study of OFDM with multipath propagation model in GNU Platform - Muslimin, Jusnaini; Asnawi, Ani Liza; Ismail, Ahmad Fadzil; Mohd. Ramli, Huda Adibah; Jusoh, Ahmad Zamani; Ibrahim, Siti Noorjannah; Mohamed Azmin, Nor Fadhillah (IEEE, 2016)
Wireless communications technology is a vast and dynamic field of study. As such, high-reconfigurable tool like software defined radio is crucially needed. Software defined radio is a set of tool that consists of RF frond-end hardware and supported software like MATLAB, GNURadio, etc. For researcher, software defined radio is important to support the frequently change configurations and requirements of the studied system in real scenario as the inflicted cost and time consumed to re-configure the embedded system are significantly high . For instance, the endless demand for better quality and service of wireless communications leads to active research in current technology like OFDM. The way OFDM been implemented is vary from one application to the other, which required a high reconfigurable tool for real scenario experimentation and analysis. Thus, for knowledge enrichment, this paper intends to study the basic approach of OFDM by providing an insight of the system in multipath propagation channels. This paper is the first part of author’s study whereas the simulation was implemented on GNU platform. The platform was used to model the OFDM system that based on both FFT and built-in GNURadio blocks, and the multipath propagation environment using the flat fading model. The observed signal constellations across the multipath models are consistent with the theoretical output, shows the reliability of GNU platform to deliver the OFDM system which will be used later for real transmission study.